Carbon nanotube cross-linked iron-nitrogen doped carbon skeleton catalyst and its preparation method and application
By using carbon nanotube cross-linked iron nitrogen doped carbon frame catalyst (Fe3C@FeNC) in zinc-air batteries, the problems of low power density and poor cycle stability in existing non-precious metal catalysts in zinc-air batteries are solved, and the effects of high power density and good cycle durability are achieved.
Patent Information
- Application Number
- CN202211039255.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-29
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing non-precious metal catalysts have low power density in zinc-air batteries, severe charge and discharge polarization, poor cycle stability, and complex bifunctional oxygen catalyst synthesis method, and poor catalytic performance.
By using carbon nanotubes and zeolite imidazole ester skeleton as precursors, a one-step method is used to synthesize carbon nanotube cross-linked iron-nitrogen doped carbon skeleton catalyst (Fe3C@FeNC). This catalyst has catalytic activity of oxidation and oxygen precipitation without using precious metals.
The high power density and good charging and discharge cycle durability of zinc-air batteries are achieved, while simplifying the catalyst preparation process and reducing production costs.
Smart Images

Figure HDA0003820324600000011 
Figure HDA0003820324600000012 
Figure HDA0003820324600000021
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalyst preparation, and in particular to a carbon nanotube cross-linked iron-nitrogen doped carbon skeleton catalyst and a preparation method and application thereof. Background Art
[0002] With the development of science and technology, environmental and energy problems such as global warming, air pollution, and depletion of natural resources are becoming more and more serious. In order to reduce the consumption of fossil fuels, it is essential to develop renewable and environmentally friendly energy and equipment. Batteries, as devices that convert chemical energy into electrical energy, are considered to be one of the most promising technologies due to their sustainability, high efficiency, and low pollution. Among various battery devices, metal-air batteries have attracted widespread attention due to their high power density and high energy density. As a potential alternative to lithium-ion batteries, zinc-air batteries have a theoretical energy density of up to 1086 Wh / kg, which is 5 times that of lithium-ion batteries. They also have unparalleled advantages such as low cost, abundant raw materials, high safety, and no environmental pollution. However, the kinetics of the oxygen reduction reaction and oxygen evolution reaction occurring on the air electrode are extremely slow, which greatly limits the commercial application of rechargeable zinc-air batteries. Although precious metal-based catalysts, such as platinum-based catalysts or ruthenium-based and iridium-based catalysts, have high catalytic activity for oxygen reduction reaction and oxygen evolution reaction, respectively, their high price, raw material scarcity, monofunctional catalysis, and poor durability have curbed their application. Therefore, it is of great significance to design new bifunctional oxygen electrocatalysts with abundant sources, low cost, high catalytic performance and environmental friendliness. Summary of the invention
[0003] In view of the above technical problems, the present invention provides a carbon nanotube cross-linked iron nitrogen doped carbon skeleton catalyst, which has excellent oxygen reduction and oxygen evolution catalytic activity.
[0004] The present invention provides a carbon nanotube cross-linked iron-nitrogen doped carbon skeleton catalyst, the general formula of the catalyst is: Fe3C@FeNC, the catalyst comprises Fe3C nanoparticles, carbon nanotubes and an iron-nitrogen doped carbon skeleton, the Fe3C nanoparticles are located in the carbon nanotubes, and the carbon nanotubes and the iron-nitrogen doped carbon skeleton are cross-linked to form a three-dimensional interpenetrating network structure.
[0005] In one embodiment, the Fe3C nanoparticles are encapsulated inside the carbon nanotube cavity.
[0006] Most of the non-precious metal catalysts in the prior art have only a single oxygen reduction or oxygen precipitation reaction catalytic function, resulting in a low power density of the zinc-air battery assembled therein, and the charge and discharge polarization is relatively serious, and the battery cycle stability is poor. In addition, the existing non-precious metal bifunctional oxygen catalyst synthesis method is relatively complicated, and compared with precious metal catalysts such as platinum and ruthenium, the catalytic performance of some non-precious metal bifunctional oxygen catalysts is not ideal. Therefore, the inventors use carbon nanotubes and zeolite imidazolate skeletons as precursors, and synthesize the above-mentioned carbon nanotube cross-linked iron nitrogen doped carbon skeleton catalyst by a one-step method, the carbon nanotubes of the catalyst are wrapped with Fe3C nanoparticles, iron single atoms are mainly loaded on the zeolite imidazolate skeleton, and the carbon nanotubes and the zeolite imidazolate skeleton are cross-linked with each other, based on the catalyst is rich in Fe-Nx oxygen reduction active sites and Fe3C nanoparticles oxygen precipitation active sites, the two active sites work synergistically, so that the catalyst can have both oxidation and oxygen precipitation catalytic activity without using precious metals. Among them, carbon nanotubes have the advantages of high conductivity and excellent chemical stability, while the evaporation of zinc in the zeolite imidazolate framework can form a rich porous structure and is conducive to the high dispersion of iron single atoms, thereby forming single-atom dispersed Fe-Nx active sites. The coexistence of rich Fe-Nx active sites and Fe3C nanoparticles enhances the catalytic activity of the oxidogen and oxygen evolution reaction. In addition, the interconnection of carbon nanotubes and iron-nitrogen doped carbon frameworks forms a three-dimensional interpenetrating network structure, which gives the catalyst strong structural stability and high electronic conductivity, which is beneficial to further reduce internal resistance and promote electron and mass transfer. Ultimately, the catalyst has excellent catalytic activity for both oxygen reduction and oxygen evolution reactions.
[0007] In one of the embodiments, the surface of the iron-nitrogen doped carbon skeleton is loaded with iron single atoms, and the iron single atoms are loaded on the surface of the iron-nitrogen doped carbon skeleton through Fe-N bonds, and the concentration of the iron single atoms is 3-5wt%.
[0008] The present invention also provides a method for preparing the catalyst, which comprises the following steps:
[0009] Preparation of oxidized carbon nanotubes: adding carbon nanotubes to an acid solution, performing acid washing and stirring, centrifuging to obtain oxidized carbon nanotube precipitation, and washing to obtain oxidized carbon nanotubes;
[0010] Preparing a precursor: preparing an oxidized carbon nanotube dispersion liquid from oxidized carbon nanotubes, adding a metal zinc salt, an imidazole derivative, and a metal iron salt to the oxidized carbon nanotube dispersion liquid to obtain a mixed solution, mixing and stirring, centrifuging to obtain a precursor precipitate, washing, and drying to obtain a precursor;
[0011] Preparation of carbon nanotube cross-linked iron-nitrogen doped carbon skeleton catalyst: placing the precursor in an inert gas atmosphere, performing heat treatment, and cooling to obtain the catalyst.
[0012] In the above preparation method, if there is no metal zinc salt and imidazole derivative, the nitrogen-doped carbon skeleton cannot be formed, and thus the Fe single atom cannot be formed, resulting in poor oxygen reduction performance; if there is no oxidized carbon nanotube, Fe3C nanoparticles cannot be formed, resulting in poor oxygen evolution activity.
[0013] In one embodiment, in the step of preparing the precursor, preparing the oxidized carbon nanotubes into an oxidized carbon nanotube dispersion comprises the following steps: ultrasonically dispersing the oxidized carbon nanotubes in water, adding a glucose solution, and ultrasonically dispersing to obtain an oxidized carbon nanotube dispersion;
[0014] The glucose is D(+)-glucose, and the concentration of the glucose solution is 50-150 mg / ml.
[0015] Without carbon nanotubes and glucose, the above reaction cannot form Fe3C nanoparticles, resulting in poor oxygen evolution activity.
[0016] In one of the embodiments, in the step of preparing the precursor, the mixing and stirring speed is 400-700 rpm, and the time is 12-15 hours; the drying step includes: drying under vacuum conditions at 60-80° C. for 10-18 hours.
[0017] In one embodiment, in the step of preparing the precursor, the cleaning includes: cleaning the precursor precipitate with water and ethanol.
[0018] In one of the embodiments, in the step of preparing the carbon nanotube cross-linked iron nitrogen doped carbon skeleton catalyst, the inert gas includes at least one of the following raw materials: nitrogen, argon; the heating rate of the heat treatment is 5-10°C / min, the temperature is 800-1000°C, and the time is 1-2h.
[0019] Heat treatment temperature is also an important condition that affects catalyst performance. Too high or too low heat treatment temperature will affect the oxygen reduction and oxygen precipitation performance of the catalyst. Only by using the above-mentioned specific high-temperature sintering process can abundant Fe-Nx and Fe3C active sites be formed.
[0020] In one embodiment, the heat treatment temperature is 900°C.
[0021] The above temperature is the optimal heat treatment temperature.
[0022] In one of the embodiments, in the step of preparing oxidized carbon nanotubes, the acid washing and stirring time is 12-18 hours and the temperature is 15-30°C.
[0023] In one embodiment, in the step of preparing oxidized carbon nanotubes, the washing comprises: washing the oxidized carbon nanotube precipitate with water and ethanol until the suspension of the oxidized carbon nanotube precipitate is neutral.
[0024] In one of the embodiments, in the step of preparing the precursor, the working concentration of the oxidized carbon nanotubes in the mixed solution is 0.3-1.5 mg / ml; the working concentration of the metal zinc salt in the mixed solution is 8-25 mg / ml, and the metal zinc salt is zinc nitrate hexahydrate; the working concentration of the imidazole derivative in the mixed solution is 15-55 mg / ml, and the imidazole derivative is 2-methylimidazole; the working concentration of the metal iron salt in the mixed solution is 2-3 mg / ml, and the metal iron salt is ferric nitrate nonahydrate; the acid solution comprises at least one of the following raw materials: sulfuric acid and nitric acid.
[0025] In one embodiment, the acid solution is a mixed solution of sulfuric acid and nitric acid, and the volume ratio of the sulfuric acid to the nitric acid is 1:(1-4).
[0026] In one embodiment, the acid solution is a mixed solution of sulfuric acid and nitric acid, the volume ratio of the sulfuric acid to the nitric acid is 1:3, the concentration of the sulfuric acid is 15-18.4 mol / L, and the concentration of the nitric acid is 14-16 mol / L.
[0027] The invention also provides a zinc-air battery, which is assembled by using the catalyst.
[0028] The zinc-air battery assembled using the above catalyst has a large power density and strong durability in the charge and discharge cycle.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] The carbon nanotube cross-linked iron nitrogen doped carbon skeleton catalyst of the present invention and its preparation method and application, the catalyst has excellent oxygen reduction and oxygen evolution catalytic activity. The zinc-air battery assembled with the catalyst exhibits a large power density and strong charge and discharge cycle durability. The preparation method of the present invention is a one-step method, simple to operate, short production cycle, and the raw materials are abundant and easy to obtain, and easy to mass produce. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a transmission electron microscopy image of the carbon nanotube cross-linked iron-nitrogen doped carbon skeleton catalyst prepared in Example 1;
[0032] Figure 2 The XRD spectrum of the carbon nanotube cross-linked iron-nitrogen doped carbon skeleton catalyst prepared in Example 1;
[0033] Figure 3 It is the oxygen evolution activity diagram of the rotating disk electrode test in the experimental example;
[0034] Figure 4 This is the oxygen reduction activity diagram of the rotating disk electrode test in the experimental example;
[0035] Figure 5 The discharge curve and power density diagram of the zinc-air battery assembled using the catalyst of Example 1 in the zinc-air battery test in the experimental example;
[0036] Figure 6 This is a cycle stability diagram of a zinc-air battery assembled using the catalyst of Example 1 in a zinc-air battery test in an experimental example. DETAILED DESCRIPTION
[0037] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0039] definition:
[0040] In the present invention, zinc-air battery refers to a new type of chemical power source that uses oxygen in the air as the positive electrode active material and metal zinc as the negative electrode active material.
[0041] source:
[0042] Unless otherwise specified, the reagents, materials, and equipment used in this example are all commercially available; the experimental methods are all conventional experimental methods in the art unless otherwise specified.
[0043] Example 1
[0044] Carbon nanotube cross-linked iron nitrogen doped carbon skeleton catalyst (Fe3C@FeNC) and preparation method thereof.
[0045] 1. Preparation of oxidized carbon nanotubes.
[0046] 50 mg of carbon nanotubes were added to a mixed solution of 2.5 ml of 18.4 mol / L sulfuric acid and 7.5 ml of 16 mol / L nitric acid, and stirred at room temperature (25°C) for 12 h. The obtained oxidized carbon nanotube suspension was centrifuged to obtain an oxidized carbon nanotube precipitate, which was washed with water and ethanol until the oxidized carbon nanotube precipitate was neutral to obtain oxidized carbon nanotubes.
[0047] 2. Prepare the precursor.
[0048] The oxidized carbon nanotubes were ultrasonically dispersed in 10 ml of deionized water for 1 h to obtain an oxidized carbon nanotube dispersion, and then 5 ml of a 150 mg / ml D(+)-glucose solution was added and ultrasonicated for 30 min. 0.5 g of zinc nitrate hexahydrate was dissolved in 10 ml of deionized water, 1.25 g of 2-methylimidazole was dissolved in 15 ml of deionized water, and 110 mg of ferric nitrate nonahydrate was dissolved in 5 ml of deionized water. The zinc nitrate solution, the 2-methylimidazole solution and the ferric nitrate solution were then added to the glucose-containing oxidized carbon nanotube dispersion in sequence to obtain a mixed solution, wherein the working concentration of the oxidized carbon nanotubes was 1.11 mg / ml, the working concentration of zinc nitrate hexahydrate was 11.11 mg / ml, the working concentration of 2-methylimidazole was 27.78 mg / ml, and the working concentration of ferric nitrate nonahydrate was 2.44 mg / ml. The mixture was stirred at a speed of 400 rpm for 15 h, centrifuged to obtain a precursor precipitate, washed once with water and ethanol respectively, and then vacuum dried in a vacuum drying oven at 60° C. for 12 h to obtain a precursor.
[0049] 3. Preparation of carbon nanotube cross-linked iron-nitrogen doped carbon skeleton catalyst.
[0050] The dried precursor was placed in a tubular furnace, argon was passed through the tube for 30 minutes to exhaust the air in the tube, and the precursor was heated to 900°C at a heating rate of 5°C / min, maintained at 900°C for 1 hour, and then naturally cooled in an argon atmosphere to obtain a carbon nanotube cross-linked iron nitrogen doped carbon skeleton catalyst.
[0051] Figure 1 This is a transmission electron micrograph of the bifunctional non-precious metal catalyst prepared in Example 1 of the present invention. From the figure, it can be seen that the carbon nanotubes and the iron-nitrogen doped carbon skeleton are interconnected. Figure 2 is the XRD spectrum of the prepared catalyst, which shows that the prepared catalyst has a large number of Fe3C active sites.
[0052] Example 2
[0053] Carbon nanotube cross-linked iron nitrogen doped carbon skeleton catalyst (Fe3C@FeNC) and preparation method thereof.
[0054] 1. Preparation of oxidized carbon nanotubes.
[0055] 50 mg of carbon nanotubes were added to a mixed solution of 2.5 ml of 18.4 mol / L sulfuric acid and 7.5 ml of 16 mol / L nitric acid, and stirred at room temperature (25°C) for 12 h. The obtained oxidized carbon nanotube suspension was centrifuged to obtain an oxidized carbon nanotube precipitate, which was washed with water and ethanol until the oxidized carbon nanotube precipitate was neutral to obtain oxidized carbon nanotubes.
[0056] 2. Prepare the precursor.
[0057] The oxidized carbon nanotubes were ultrasonically dispersed in 10 ml of deionized water for 1 h to obtain an oxidized carbon nanotube dispersion, and then 5 ml of a 100 mg / ml D(+)-glucose solution was added and ultrasonicated for 30 min. 1 g of zinc nitrate hexahydrate was dissolved in 10 ml of deionized water, 2.25 g of 2-methylimidazole was dissolved in 15 ml of deionized water, and 125 mg of ferric nitrate nonahydrate was dissolved in 5 ml of deionized water. The zinc nitrate solution, the 2-methylimidazole solution and the ferric nitrate solution were then added to the oxidized carbon nanotube dispersion containing glucose in sequence to obtain a mixed solution, wherein the working concentration of the oxidized carbon nanotubes was 1.11 mg / ml, the working concentration of the zinc nitrate hexahydrate was 22.22 mg / ml, the working concentration of the 2-methylimidazole was 50 mg / ml, and the working concentration of the ferric nitrate nonahydrate was 2.78 mg / ml. The mixture was stirred at a speed of 400 rpm for 15 h, centrifuged to obtain a precursor precipitate, washed once with water and ethanol respectively, and then vacuum dried in a vacuum drying oven at 60° C. for 12 h to obtain a precursor.
[0058] 3. Preparation of carbon nanotube cross-linked iron-nitrogen doped carbon skeleton catalyst.
[0059] The dried precursor was placed in a tubular furnace, argon was passed through the tube for 30 minutes to exhaust the air in the tube, and the precursor was heated to 900°C at a heating rate of 5°C / min, maintained at 900°C for 1 hour, and then naturally cooled in an argon atmosphere to obtain a carbon nanotube cross-linked iron nitrogen doped carbon skeleton catalyst.
[0060] Example 3
[0061] Carbon nanotube cross-linked iron nitrogen doped carbon skeleton catalyst (Fe3C@FeNC) and preparation method thereof.
[0062] 1. Preparation of oxidized carbon nanotubes.
[0063] 25 mg of carbon nanotubes were added to a mixed solution of 2.5 ml of 18.4 mol / L sulfuric acid and 7.5 ml of 16 mol / L nitric acid, and stirred at room temperature (25°C) for 12 h. The obtained oxidized carbon nanotube suspension was centrifuged to obtain an oxidized carbon nanotube precipitate, which was washed with water and ethanol until the oxidized carbon nanotube precipitate was neutral to obtain oxidized carbon nanotubes.
[0064] 2. Prepare the precursor.
[0065] The oxidized carbon nanotubes were ultrasonically dispersed in 10 ml of deionized water for 1 h to obtain an oxidized carbon nanotube dispersion, and then 5 ml of 80 mg / ml D(+)-glucose solution was added and ultrasonicated for 30 min. 0.5 g of zinc nitrate hexahydrate was dissolved in 10 ml of deionized water, 0.95 g of 2-methylimidazole was dissolved in 15 ml of deionized water, and 100 mg of ferric nitrate nonahydrate was dissolved in 5 ml of deionized water. The zinc nitrate solution, the 2-methylimidazole solution and the ferric nitrate solution were then added to the oxidized carbon nanotube dispersion containing glucose in sequence to obtain a mixed solution, wherein the working concentration of the oxidized carbon nanotubes was 0.56 mg / ml, the working concentration of zinc nitrate hexahydrate was 11.11 mg / ml, the working concentration of 2-methylimidazole was 21.11 mg / ml, and the working concentration of ferric nitrate nonahydrate was 2.22 mg / ml. The mixture was stirred at a speed of 400 rpm for 12 h, centrifuged to obtain a precursor precipitate, washed once with water and ethanol respectively, and then vacuum dried in a vacuum drying oven at 60° C. for 12 h to obtain a precursor.
[0066] 3. Preparation of carbon nanotube cross-linked iron-nitrogen doped carbon skeleton catalyst.
[0067] The dried precursor was placed in a tubular furnace, argon was passed through the tube for 30 minutes to exhaust the air in the tube, and the precursor was heated to 900°C at a heating rate of 5°C / min, maintained at 900°C for 1 hour, and then naturally cooled in an argon atmosphere to obtain a carbon nanotube cross-linked iron nitrogen doped carbon skeleton catalyst.
[0068] Comparative Example 1
[0069] An iron-nitrogen doped carbon skeleton catalyst (FeNC) and a preparation method thereof.
[0070] 0.5g zinc nitrate hexahydrate was dissolved in 10ml deionized water, 1.25g 2-methylimidazole was dissolved in 15ml deionized water, 110mg ferric nitrate nonahydrate was dissolved in 5ml deionized water, and then the zinc nitrate solution and ferric nitrate solution were added to the 2-methylimidazole solution, stirred at 400rpm for 15h, the suspension was centrifuged, the solid precipitate was washed with water and ethanol respectively, and then vacuum dried in a vacuum drying oven at 60°C for 12h. The dried precursor was placed in a tube furnace, argon was passed through for 30min to exhaust the air in the tube, and heated to 900°C at a heating rate of 5°C / min, maintained at 900°C for 1h, and then naturally cooled in an argon atmosphere to obtain an iron-nitrogen doped carbon skeleton catalyst (FeNC).
[0071] Comparative Example 2
[0072] An iron-doped carbon nanotube catalyst (FeNPs) and a preparation method thereof.
[0073] 1. Preparation of oxidized carbon nanotubes.
[0074] 25 mg of carbon nanotubes were added to a mixed solution of 2.5 ml of 18.4 mol / L sulfuric acid and 7.5 ml of 16 mol / L nitric acid, and stirred at room temperature (25°C) for 12 h. The obtained oxidized carbon nanotube suspension was centrifuged to obtain an oxidized carbon nanotube precipitate, which was washed with water and ethanol until the oxidized carbon nanotube precipitate was neutral to obtain oxidized carbon nanotubes.
[0075] 2. Prepare the precursor.
[0076] The oxidized carbon nanotubes were ultrasonically dispersed in 10 ml of deionized water for 1 hour to obtain an oxidized carbon nanotube dispersion, and then 5 ml of 150 mg / ml D(+)-glucose solution was added and ultrasonicated for 30 minutes. 110 mg of ferric nitrate nonahydrate was dissolved in 5 ml of deionized water, and then poured into the oxidized carbon nanotube dispersion containing glucose, stirred at 400 rpm for 15 hours, centrifuged to obtain a precursor precipitate, washed once with water and ethanol respectively, and then vacuum dried in a vacuum drying oven at 60°C for 12 hours to obtain a precursor.
[0077] 3. Preparation of iron-doped carbon nanotube catalysts.
[0078] The dried precursor was placed in a tubular furnace, argon was passed through the tube for 30 minutes to exhaust the air in the tube, and the precursor was heated to 900°C at a heating rate of 5°C / min, maintained at 900°C for 1 hour, and then naturally cooled in an argon atmosphere to obtain an iron-doped carbon nanotube catalyst.
[0079] Experimental example
[0080] 1. Rotating disk electrode test.
[0081] 1. Test method.
[0082] The Fe3C@FeNC prepared in Examples 1-3 was subjected to a rotating disk electrode test at a speed of 1600 rpm. The oxygen reduction activity was evaluated in an oxygen-saturated 0.1 M KOH solution, and the oxygen evolution activity was evaluated in an oxygen-saturated 1 M KOH solution. A commercially available precious metal catalyst Pt / C-IrO2 (TANAKA Precious Metals), and the catalysts of Comparative Example 1 and Comparative Example 2 were taken as control examples and tested under the same conditions.
[0083] 2. Test results.
[0084] The test results are shown in the following table and Figure 3 , Figure 4 As shown, Figure 3 is the oxygen evolution activity diagram, Figure 4 The oxygen reduction activity diagram.
[0085] Table 1 Rotating disk electrode test results
[0086] <![CDATA[E 1 / 2 (V vs RHE)]]> <![CDATA[E j=10 (V vs RHE)]]> ΔE(V) Example 1 0.856 1.450 0.594 Example 2 0.856 1.559 0.703 Example 3 0.835 1.498 0.663 Comparative Example 1 0.794 1.739 0.945 Comparative Example 2 0.752 1.530 0.778 <![CDATA[Pt / C-IrO2]]> 0.841 1.519 0.678
[0087] It can be seen from the above table that the FeNC prepared in comparative example 1 exhibits good oxygen reduction catalytic activity, but its oxygen evolution catalytic activity is very poor. The FeNPs prepared in comparative example 2 exhibit good oxygen evolution catalytic activity, but its oxygen reduction catalytic activity is very poor. The Fe3C@FeNC prepared in examples 1 to 3 all exhibit excellent oxygen reduction and oxygen evolution catalytic activity, indicating that the coexistence of abundant Fe-Nx active sites and Fe3C nanoparticles has a significant effect on enhancing the catalytic activity of oxygen reduction and oxygen evolution reactions. Figure 3 , Figure 4 As shown in the figure, the oxygen reduction reaction half-wave potential (E 1 / 2 ) reaches 0.856Vvs.RHE, and the oxygen evolution reaction is 10mA / cm 2 Current density (E j=10 ) reaches 1.450V vs.RHE, and its comprehensive performance (the potential difference ΔE between the above two potentials) is as low as 0.594V, which is better than 0.678V of the precious metal catalyst Pt / C-IrO2.
[0088] 2. Zinc-air battery testing.
[0089] 1. Test method.
[0090] The Fe3C@FeNC prepared in Example 1 was loaded on a foam nickel-porous carbon paper gas diffusion layer as an air electrode, a zinc plate was used as an anode, and a 6M KOH aqueous solution containing 0.2M Zn(OAc)2 was used as an electrolyte to perform a zinc-air battery test. A commercially available precious metal catalyst Pt / C-IrO2 (TANAKA Precious Metals) was used as a control example and assembled and tested under the same conditions.
[0091] 2. Test results.
[0092] Test results such as Figure 5 and Figure 6 The maximum power density of the zinc-air battery based on Fe3C@FeNC reaches 178mW / cm 2 , better than Pt / C-IrO2 (171mW / cm 2 ). In the charge-discharge cycle test, compared with the zinc-air battery based on Pt / C-IrO2, the zinc-air battery based on Fe3C@FeNC showed a constant current charge-discharge cycle of up to 225h, showing better durability.
[0093] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0094] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a carbon nanotube cross-linked iron-nitrogen doped carbon skeleton catalyst, characterized in that: The preparation method comprises the following steps: Preparation of oxidized carbon nanotubes: adding carbon nanotubes to an acid solution, performing acid washing and stirring, centrifuging to obtain oxidized carbon nanotube precipitation, and washing to obtain oxidized carbon nanotubes; Preparing a precursor: ultrasonically dispersing oxidized carbon nanotubes in water, adding a glucose solution, and ultrasonically dispersing to obtain an oxidized carbon nanotube dispersion, adding a metal zinc salt, an imidazole derivative, and a metal iron salt to the oxidized carbon nanotube dispersion to obtain a mixed solution, mixing and stirring, centrifuging to obtain a precursor precipitate, washing, and drying to obtain a precursor; Preparation of carbon nanotube cross-linked iron nitrogen doped carbon skeleton catalyst: placing the precursor in an inert gas atmosphere, performing heat treatment, and cooling to obtain; the heating rate of the heat treatment is 5-10°C / min, the temperature is 800-1000°C, and the time is 1-2h; The general formula of the carbon nanotube cross-linked iron nitrogen doped carbon skeleton catalyst is: Fe3C@FeNC, which includes Fe3C nanoparticles, carbon nanotubes and iron nitrogen doped carbon skeletons, wherein the Fe3C nanoparticles are located in the carbon nanotubes, and the carbon nanotubes and the iron nitrogen doped carbon skeletons are cross-linked to form a three-dimensional interpenetrating network structure; the surface of the iron nitrogen doped carbon skeleton is loaded with iron single atoms, and the iron single atoms are loaded on the surface of the iron nitrogen doped carbon skeleton through Fe-N bonds, and the concentration of the iron single atoms is 3-5wt%.
2. The preparation method according to claim 1, characterized in that: The glucose is D(+)-glucose, and the concentration of the glucose solution is 50-150 mg / ml.
3. The preparation method according to claim 1, characterized in that: In the step of preparing the precursor, the mixing and stirring speed is 400-700 rpm for 12-15 hours; the drying step includes: drying under vacuum conditions at 60-80° C. for 10-18 hours.
4. The preparation method according to claim 1, characterized in that: In the step of preparing the carbon nanotube cross-linked iron-nitrogen doped carbon skeleton catalyst, the inert gas includes at least one of the following raw materials: nitrogen and argon.
5. The preparation method according to claim 1, characterized in that: In the step of preparing oxidized carbon nanotubes, the acid washing and stirring time is 12-18 hours, and the temperature is 15-30°C.
6. The preparation method according to claim 1, characterized in that: In the step of preparing the precursor, the working concentration of the oxidized carbon nanotubes in the mixed solution is 0.3-1.5 mg / ml; the working concentration of the metal zinc salt in the mixed solution is 8-25 mg / ml, and the metal zinc salt is zinc nitrate hexahydrate; the working concentration of the imidazole derivative in the mixed solution is 15-55 mg / ml, and the imidazole derivative is 2-methylimidazole; the working concentration of the metal iron salt in the mixed solution is 2-3 mg / ml, and the metal iron salt is ferric nitrate nonahydrate; In the step of preparing oxidized carbon nanotubes, the acid solution includes at least one of the following raw materials: sulfuric acid and nitric acid.
7. The preparation method according to claim 6, characterized in that: The acid solution is a mixed solution of sulfuric acid and nitric acid, and the volume ratio of the sulfuric acid to the nitric acid is 1:(1-4).
8. The carbon nanotube cross-linked iron-nitrogen doped carbon skeleton catalyst obtained by the preparation method according to any one of claims 1 to 7.
9. A zinc-air battery, characterized in that: The zinc-air battery is assembled using the catalyst described in claim 8.